Implementing the Triple Bottom Line Concept in Islamic Sustainable Fashion Business at Maison Gadiza Indonesia - Khoirunnisa, Fitri; Maulidizen, Ahmad (FASTABIQ: JURNAL STUDI ISLAM, 2024)
Indonesia has aimed to establish itself as the global hub for Islamic fashion since 2016. Despite producing a significant volume of fashion, particularly in textiles, the country has yet to achieve this goal by 2020. Moreover, the waste generated from fashion production has had adverse effects. To address these challenges and enhance its competitive edge in global Muslim fashion, Indonesia sees fashion sustainability as a crucial solution, offering a more sustainable approach compared to fast fashion. This study focuses on Maison Gadiza's adoption of the Triple Bottom Line (TBL) concept to explore how it is implemented. It examines the application of TBL from Islamic perspectives and delves into the challenges and opportunities within the Islamic sustainability fashion business. Using qualitative methods such as interviews, observations, and analysis of Maison Gadiza's documentation, the research reveals that Maison Gadiza integrates the TBL concept with a focus on People, Planet, and transforming Profit into blessings. These blessings hold significant value not only in this world but also in the hereafter, aligning with Islamic values. However, the study identifies challenges stemming from market trends that influence consumer behaviors, such as extensive discount offers and promotional campaigns. On the other hand, Maison Gadiza sees opportunities in the growing awareness among today's youth for eco-friendly products and brands, as well as increasing global support for sustainability initiatives